Productivity potential and profitability of whole package technology in oilseed crops: PRODUCTIVITY POTENTIAL AND PROFITABILITY OF WHOLE PACKAGE TECHNOLOGY IN OILSEEDS - G D S KUMAR; A VISHNUVARDHAN REDDY; S V RAMANA RAO (Journal of Oilseeds Research, 2020)
The productivity of oilseed crops in India is low due to rainfed cultivation, small operational land holdings, lack of varietal replacement (groundnut and sesame), losses due to biotic and abiotic stresses and low adoption of agronomic practices and other improved technologies. There is a potential to increase productivity of oilseeds by using best production practices and right combination of inputs at right time. Several technologies were developed by the All India Coordinated Research Projects (AICRP) on oilseed crops that can significantly increase the productivity of oilseeds. Realizing the importance of extending these technologies to farmers, frontline demonstrations (FLDs) were conducted. Data from a total of 24,035 FLDs conducted on whole package technology over an area of 9727 ha in nine oilseed crops in different agro-ecological situations of the country during 2014-15 to 2018-19 were analyzed in this paper. The results showed increased yield, gross monetary returns and additional net returns with improved technologies (IT) as compared to farmers' practices. The benefit cost ratio was also higher indicating the profitability of improved technology. In order to speed up the adoption of improved technologies by farmers, there is a need to provide timely access to key inputs like, quality seeds of high yielding cultivars and availability of agro-chemicals in time at village level. There is also a need to forge required partnerships involving extension agencies, state departments of agriculture and input agencies in educating the farmers on the impact of improved technologies, organizing exposure visits to model farms and ensuring timely availability of quality inputs to enhance oilseed productivity and profitability.